Postlarval stages and growth patterns of the spider crab Pyromaia tuberculata (Brachyura, Majidae) from laboratory-reared material - Flores, AAV; Marques, FPL; Negreiros-Fransozo, M. L. (Crustacean Soc, 2002)
The spider crab Pyromaia tuberculata was introduced into southeastern Brazil; ovigerous material was collected and reared in the laboratory. Morphologic changes and growth patterns of post-larval development are reported. Results show that within-stage size variation is lowest in mature stages, especially in the case of females in which there is an apparent size threshold for the last juvenile stages to undergo the puberty molt. A prepuberty molt taking place at the fourth crab stage is indicated by analyzing the allometric growth of the abdomen in females. In contrast, the same procedure using the allometric growth of chelae failed in detecting both the prepuberty and puberty molts in males. Conversely to females, which develop a complex brood chamber at the puberty molt, the enlargement of chelae was not consistent in all postpuberty males. The short instar sequence of this species, in no case exceeding nine stages, is marked by conspicuous morphologic alterations achieved at each molt. Almost all stages can be identified by examining diagnostic features of rostrum, abdomen, sternum, and pleopods.